(untitled) (Jalalabad Medical Journal, 2026)
Cholelithiasis, a common gastrointestinal condition, is influenced by various factors, including age, gender, BMI, and genetic predisposition. This study aimed to assess the distribution of age, gender and BMI among patients diagnosed with cholelithiasis in Sylhet. A cross-sectional study was conducted from January to June 2022 at Popular Medical Centre and Hospital in Sylhet, involving 200 cholelithiasis patients confirmed through imaging studies. Data were collected through face-to-face interviews, physical examinations, and medical records review. Variables such as age, gender, BMI, the ABO blood group, and family history of gallbladder disease were analysed using descriptive statistics. Among the 200 patients, females (65.5%) were more affected than males (34.5%), with a male-to-female ratio of 1:1.9. The mean age was 45.10±14.30 years, with the highest prevalence in the 48-57 years age group (25.5%). Most patients (50%) had a BMI within the normal range (18.5-24.9), while 46% were underweight (<18.4). Blood group O was predominant (39.5%), followed by B (32%) and A (24%). A positive family history of gallbladder disease was reported by 51% of patients. Cholelithiasis was more prevalent in middle-aged females, with most patients having normal or underweight BMI. Blood group O and a family history of gallbladder disease were significant risk factors. Larger studies with extended follow-ups are needed to confirm these findings. Jalalabad Med J 2025; 22 (1): 33-36.